The galectin-3 inhibitor selvigaltin reduces liver inflammation and fibrosis in a high fat diet rabbit model of metabolic-associated steatohepatitis - Comeglio, Paolo; Guarnieri, Giulia; Filippi, Sandra; Cellai, Ilaria; Acciai, Gabriele; Holyer, Ian; Zetterberg, Fredrik; Leffler, Hakon; Kahl-Knutson, Barbro; Sarchielli, Erica; Morelli, Annamaria; Maggi, Mario; et al. (Frontiers in Pharmacology, 2024)
Introduction. Galectin-3 is a pro-fibrotic β-galactoside binding lectin highly expressed in fibrotic liver and implicated in hepatic fibrosis. Selvigaltin (previously known as GB1211) is a novel orally active galectin-3 small molecule inhibitor that has high affinity for galectin-3 (human KD=25 nM; rabbit KD=12 nM) and high oral bioavailability in rabbits and man. In this study the efficacy of selvigaltin was investigated in a high fat diet (HFD) rabbit model of metabolic-associated steatohepatitis (MASH). Methods. Male New Zealand White rabbits were individually caged under standard conditions in a temperature and humidity-controlled room on a 12h light/darkness cycle. After 1 week of regular diet (RD), rabbits were randomly assigned for 8 or 12 weeks to different groups: RD/vehicle, RD/selvigaltin, HFD (8 weeks), HFD/vehicle and HFD/selvigaltin (0.3, 1.0, 5.0 or 30 mg/kg selvigaltin with vehicle/selvigaltin p.o. dosed therapeutically q.d. 5 days per week from week 9 or 12). Liver inflammation, steatosis, ballooning, and fibrosis was measured via blood metabolic markers, histomorphological evaluation [Oil Red O, Giemsa, Masson's trichome, picrosirius red (PSR) and second harmonic generation (SHG)], and mRNA and protein expressionand mRNA expression. Results.Steatosis, inflammation, ballooning, and fibrosis were all increased from RD to HFD/vehicle groups.Selvigaltin demonstrated target engagement by significantly decreasing galectin-3 levels in the liver as measured via immunohistochemistry and mRNA analysis. Selvigaltin dose-dependently reduced biomarkers of liver function (AST, ALT, bilirubin), inflammation (cells foci), and fibrosis (PSR, SHG), as well as decreasing the mRNA and protein expression of several key inflammation and fibrosis biomarkers (e.g., IL6, TGFβ3, SNAI2, collagen)as well as decreasing the mRNA expression of several key inflammation and fibrosis biomarkers (e.g., IL6, TGFβ3, SNAI2). Doses of 1.0 or 5.0 mg/kg demonstrated consistent efficacy across most biological endpoints supporting the current clinical doses of selvigaltin being investigated in liver disease.Discussion. Selvigaltin significantly reduced hepatic inflammation and fibrosis in an HFD rabbit model of MASH following therapeutic dosing for 4 weeks in a dose-dependent manner. These data support the human selvigaltin dose of 100 mg b.i.d. that has been shown to reduce key liver biomarkers during a clinical study in liver cirrhosis.